Perancangan Sistem Informasi Pengolahan Nilai Siswa Berbasis Website Menggunakan Metode Agile (studi kasus: Smk Bintang Nusantara) - Juliana Tumanggor; Rizky Fauzi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Student grade management is a crucial component of academic administration that requires accuracy, consistency, and structured data handling. At SMK Bintang Nusantara, the grading process is still conducted manually through separate document submissions by subject teachers, resulting in delays, data inconsistencies, and difficulties in grade recapitulation by homeroom teachers. This study aims to design and develop a website-based student grade processing information system using the Agile method to enhance efficiency, accuracy, and accessibility of academic data management. The research employed an iterative Agile approach consisting of requirements analysis, system design, implementation, and testing conducted in repeated cycles to incorporate user feedback. Data were collected through interviews, observation, and literature review. The system was developed using PHP and MySQL with a centralized database structure and evaluated through Black Box Testing to ensure functional reliability. The results indicate that the system standardizes grade input by teachers, facilitates verification by homeroom teachers, and generates digital report cards accessible to administrators, students, and parents. The centralized database improves data security and minimizes redundancy. The implementation of Agile methodology provides flexibility in adapting system features to user requirements. Overall, the proposed system improves the efficiency of grade processing and supports the digital transformation of academic administration at SMK Bintang Nusantara.